A Systematic Review of Alternative Service Delivery in Africa for Taming Wicked Risks - Nel-Sanders, Danielle (Center for Risk Management & Sustainability and RSF Press, 2024)
This research considers the role that alternative service delivery can play in addressing wicked problems. The aim of this research is, firstly, to determine which evidence and knowledge are available on alternative service delivery arrangements relevant to African countries to inform decisions about addressing wicked problems on the continent. Second, this research determines suitable mechanisms for an alternative service delivery model for mitigating wicked risks in Africa. This research is based on a systematic literature review. This systematic literature review reveals that most work on alternative service delivery has been done in developed countries, with developing African countries being left behind in research on alternative service delivery. Furthermore, most of the alternative service delivery efforts have not focused on addressing wicked problems. A large number of articles on alternative service delivery models show that alternative delivery is not a preferred approach in Africa. This research recommends an alternative service delivery model that is based on digital governance, service delivery innovation and partnerships. Robust governance responses are needed to mitigate these wicked risks, and alternative service delivery presents robust features to mitigate these risks given that it is more flexible, agile, adaptable, and decentralized in nature than simply relying on traditional government responses. Lastly, risk-informed decision-making should be placed at the center of the reform agenda for a smart and sustainable society.